Time Division Switching Scheme and Performance Analysis of Low Orbit Quantum Satellite Communication - Guang Yang; Min Nie; Fan Jiang (Dianxin kexue)
Low orbit quantum satellite system is used to realize a worldwide secure communication. To solve the problem of multiple quantum users' access and information transmission in satellite coverage, a multi-beam time division quantum switching scheme was proposed, and a detailed description of the structure and working process of the time division quantum switch were given. In different time slot, the switch set up a quantum entanglement swapping channel for different users to transmit their quantum information. To overcome the delay in satellite-earth link and satellite-satellite link, a switching and transmission method was proposed based on quantum channel byte, which decreased the average qubit transmission delay for single time slot. Performance analysis shows that the number of time slot and the length of quantum channel byte have the key influence on the user number, the traffic and the call of loss. In certain channel conditions, by rational designing of these parameters, the quantum satellite communication system can meet the demanded service requirements.